1997
DOI: 10.1103/physrevc.56.839
|View full text |Cite
|
Sign up to set email alerts
|

Variational approach to anharmonic collective motion

Abstract: We derive large-amplitude collective equations of motion from the variational principle for the time-dependent Schroedinger equation. These equations reduce to the well-known diabatic formulas for vibrational frequencies in the small amplitude limit. The finite amplitude expression allows departures from harmonic behavior of giant resonances to be simply estimated. The relative shift of the second phonon falls with nuclear mass A as A^(-4/3) in the three modes we consider: monopole, dipole, and quadrupole. Num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 32 publications
8
42
0
Order By: Relevance
“…Similar expressions for momentum [23] and for mass (see for instance [24][25][26]) are also found in literature.…”
Section: Mass and Momentum Associated With Collective Coordinatesupporting
confidence: 54%
“…Similar expressions for momentum [23] and for mass (see for instance [24][25][26]) are also found in literature.…”
Section: Mass and Momentum Associated With Collective Coordinatesupporting
confidence: 54%
“…In fact, anharmonicities influence electromagnetic DGDR cross sections in several ways: (a) the energy shifts of the DGDR states from the harmonic values can affect in an important way the electromagnetic cross section, in keeping with the exponential dependence of these quantities with the Q value of the process [22], (b) anharmonicities lead to changes in the E1 transition matrix elements to preserve the energy weighted sum rule (EWSR) [23] which eventually reinforce these effects, (c) anharmonicities which are a consequence of the mixing of states with different number of phonons give rise to many paths, other than the (harmonic) two-step one, to excite the DGDR in electromagnetic processes. While all these questions inspired much theoretical work [24][25][26][27][28][29][30][31][32][33][34], no clear picture has emerged of the DGDR anharmonicity question, let alone an explanation of the "Coulomb excitation anomaly." In particular, no consensus exists concerning the mass-number dependence of the energy shifts from the harmonic values.…”
Section: (Received 15 May 2000)mentioning
confidence: 99%
“…The anharmonic behavior of the giant resonances as a possibility to explain the increase of the Coulomb excitation cross sections has been studied by several authors 23,24 (see also ref. 25 , and references therein). It was found that the effect is indeed negligible and it could be estimated 25 as ∆ (2) E < E GDR /(50A) ∼ A −4/3 MeV.…”
Section: Anharmonicitiesmentioning
confidence: 99%